The creation of ideological discourse in the popular cinema of ‘tardofranquismo’ (1966-1975): ‘Paco Martínez Soria”s season’ (Communication & Society, 2012)
The popular films of the last years of Franco regime had an outstanding commercial success because of movies that, under the guise of a simple entertainment, reflected a specific image about that historical period of change. The production during ‘tardofranquismo’ found a vein in certain groups of works, among which stand out the ten films starring by actor Paco Martínez Soria. His filmography enables an ideological interpretation: defense of tradition against any kind of novelty, thanks to a benevolent father figure who ensures the stability of the communities he belongs to.